Towards "Good" Native Land Governance: An Evaluation in Sarawak, Malaysia - Liat Choon, Tan; Ming Liang, Toh; kam Seng, Looi; Wee Vern, Tan; bin Ujang, Muhamad Uznir; Ai Chin, Thoo; binti Azri, Nor Suhaibah; Kathitasapathy, Shanmugapathy A. L. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Sarawak is the largest state in Malaysia, where two-thirds of the population are Indigenous. This study aims to evaluate, through the lens of good governance principles, the current practice of the Sarawak State’s formal land governance of lands associated with Native Customary Rights (hereafter known as Native land governance). Being quantitative in nature, this study conceptualises an evaluation framework for good governance principles as applied to Native land governance. Next, this study empirically tests out the framework by adopting a multi-criteria decision-making tool known as The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). TOPSIS analysis enables the integration of perceptions between State/private groups and Indigenous groups. The output of the TOPSIS analysis is summarised in a strength, weakness, opportunity, and threat (SWOT) format according to the TOPSIS closeness value. Unfortunately, results show that the weaknesses outnumber the strengths in Sarawak’s Native land governance. Among these issues, Indigenous respondents highlight major issues with the Sarawak land registry’s efficiency in delivering outcomes that are equitable for Indigenous land rights. This study ends with recommendations on how the state of Sarawak can move towards compliance with good governance principles in relation to lands associated with Native Customary Rights.